Halal Risk Analysis of Snake Fruit (Salacca Zalacca) Processing Industry using Fishbone Diagram - Lukman Adhitama; Arina Rijki Aulia; Farah Asifi Elkhanna; Akbar Kurniawan (Journal of Halal Research, Policy, and Industry, 2023)
Innovation that continues to develop in the culinary industry also requires business actors to pay attention to the quality of the products they produce. One of the things that needs to be considered as part of product quality assurance is the halalness of the product itself. The importance of the halal aspect of products requires the Salak Turi Small Medium Enterprise (SME) Small and Medium Enterprise (SME) to pay attention to the palak products they produce. Through this research, results were obtained that the halal product guarantee has not been fully implemented. The results of mapping using a fishbone diagram show that there are 10 risks that have the potential to disrupt the halal guarantee of products produced by Salak Turi SME. These risks are divided into 5 categories, namely man, material, method, equipment and environment. To ensure the halalness of the palak products produced by Salak Turi SME, it is necessary to improve by mitigating the risks that occurred on their industry.